The Impact of Gamification on Repurchase Intention in E-commerce Platforms and the Mediating Effect of Brand Attitude: in the Case of Shopee Indonesia - Natalien Valerry; Alicia Mulyono (iBuss Management, 2022)
The transcendent growth of e-commerce has elevated firm rivalry to strive for a significant share in Indonesia’s market. Various marketing strategies have been utilized to advance engagement and transactions in the e-commerce platform. Shopee, a leading e-commerce platform in Indonesia, has built a holistic gamified experience to leverage brand presence and repetitive purchases on the platform. Hence, the researchers would like to study gamification influence through modified Technology Acceptance Model (TAM), incorporating perceived usefulness, perceived ease of use, perceived social influence, and perceived enjoyment as the variables affecting repurchase intention in Shopee Indonesia. This study will also analyze whether brand attitude mediates gamification behavioral intention and repurchase intention. This research is done through a quantitative approach using simple random sampling. After distributing the online questionnaire, 132 valid respondents were analyzed using SmartPLS to assess the relationship between the variables. Findings show that perceived ease of use and perceived social influence significantly influence repurchase intention, whereas perceived usefulness and perceived enjoyment do not significantly influence repurchase intention. Further, findings show that brand attitude mediates the relationship between perceived ease of use and perceived enjoyment to repurchase intention but does not mediate perceived usefulness and perceived social influence to repurchase intention.  Keywords: E-commerce, Gamification, Brand attitude, Repurchase intention, Perceived usefulness, Perceived ease of use, Perceived social influence, Perceived enjoyment